2017
DOI: 10.1177/1055665617718549
|View full text |Cite
|
Sign up to set email alerts
|

Examining Age, Sex, and Race Characteristics of Velopharyngeal Structures in 4- to 9-Year-Old Children Using Magnetic Resonance Imaging

Abstract: The purpose of this study was to quantify the growth of the various craniofacial and velopharyngeal structures and examine sex and race effects. Methods: Eight-five healthy children (53 white and 32 black) with normal velopharyngeal anatomy between 4 and 9 years of age who met the inclusion criteria and successfully completed the magnetic resonance imaging (MRI) scans were included in the study. Results: Developmental normative mean values for selected craniofacial and velopharyngeal variables by race and sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 52 publications
10
44
0
Order By: Relevance
“…Changes in velar shape are likely due to growth of the velum as children mature. Previous studies have reported that growth led to increased velar length and velar thickness 2223. These anatomical changes likely result in the presence of certain velar shapes in adults.…”
Section: Discussionmentioning
confidence: 92%
“…Changes in velar shape are likely due to growth of the velum as children mature. Previous studies have reported that growth led to increased velar length and velar thickness 2223. These anatomical changes likely result in the presence of certain velar shapes in adults.…”
Section: Discussionmentioning
confidence: 92%
“…Preliminary studies have demonstrated the validity and reliability of using MRI protocols in young children with normal anatomy (Tian et al, 2010a; Tian et al, 2010b; Kollara et al, 2016; Perry et al, 2017; Perry et al, 2018). Because no significant differences have been reported regarding the position in which MRI data are collected, participants were imaged in the supine position (Perry, 2011; Kollara and Perry, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Children with 22q11DS were recruited through use of flyers that were disseminated and posted on social media sites to make available to all patients who met the following inclusion criteria: (1) diagnosis of 22q11.2 deletion as confirmed by fluorescence in situ hybridization analysis or microarray, (2) between 4 and 12 years of age, (3) have a negative history of overt cleft or other genetic disorders, and (4) were no less than 6 months post adenoidectomy or tonsillectomy. Individuals with normal velopharyngeal and craniofacial anatomy were selected from a larger data set (Perry et al, 2018) and were chosen because they represented individuals who were similar in age to those in the 22q11DS group. Parents of the participants in the control group indicated no history of hearing loss, chronic ear infections, ear infections at the time of the study, or prior surgeries.…”
Section: Participantsmentioning
confidence: 99%